Deteccion de B-exotoxina en cepas nativas de Bacillus thuringiensis por HPLC - Baro Robaina, Y.=700 1 Linares Jimenez, C.; Dieksmeier Corcuera, G.
(Es, En)
Ilus., 11 ref.
Keywords: BACILLUS THURINGIENSIS; EXOTOXINAS; HPLC; CUBA; DETECCION DE B-EXOTOXINA